Miss Scarlet & the Duke. Season two [videorecording (DVD)] - New, Rachael (PBS Distribution, 2022)
It's a few months after the end of Season One. Eliza Scarlet has solved her father's murder while her relationship with Inspector William Wellington, aka the Duke, continues to slowly simmer.